Pontificia Praecepta de Clero Uxorato Orientali and the optionality of celibacy in the Eastern Catholic Churches - TANASIYCHUK, ANDRIY (Prawo Kanoniczne, 2016)
The article concerns the document of the Congregation for the Eastern Churches Pontificia Praecepta de Clero Uxorato Orientali published on 14 June 2014, under which outside the traditional Eastern territories within the meaning of the law of the Eastern Catholic Churches, and where the Eastern Catholics reside, the married men can be ordained. The author analyzes the content of the document, explains the terminological problems and its place in the system of canon law, taking up the problematic issues.